Generation of a pregnancy cohort for medicine utilisation and medicine safety studies in New Zealand. Issue 12 (5th November 2018) - Donald, Sarah; Barson, David; Horsburgh, Simon; Sharples, Katrina; Parkin, Lianne
Abstract: Purpose: The aim of this study was to use national health databases to assemble a pregnancy cohort for undertaking medicine utilisation and safety studies in New Zealand. Method: Pregnancies conceived between January 2005 and March 2015 were identified in the National Maternity Collection, the National Minimum Dataset, the Mortality Collection, and the Laboratory Claims Collection. Pregnancy start and end dates were calculated and used in conjunction with the National Health Index number to merge the records from the four collections to create the New Zealand Pregnancy Cohort. Records of live born and stillborn infants identified in the National Maternity Collection and the Mortality Collection that were linkable with a cohort member formed the baby cohort. Results: The cohort consists of 941 468 pregnancies to 491 272 women. One‐third of the pregnancies, predominantly early pregnancy losses and terminations, were not found in the National Maternity Collection. Records of 632 090 live born or stillborn infants are linked with 623 099 pregnancies. Conclusions: The New Zealand Pregnancy Cohort is a comprehensive collection of virtually all pregnancies which ended in a live or stillbirth and many, though not all, which ended as early pregnancy losses or terminations in New Zealand over the past decade, and better represents the pregnant population than a cohort generated from the National Maternity Collection alone would do. This cohort will be valuable for investigating patterns of medicine use during pregnancy in New Zealand and developing a fuller understanding of potential impacts of foetal exposure in early pregnancy.